Analysis of The Influence of Sharia Monetary Operations Instruments on Gross Domestic Product in Indonesia in The Perspective of Islamic Economics in 2019-2023 - Diah Salsyarani; Asriani; Yulistia Devi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Islamic monetary operation instruments on gross domestic product. The results of the study indicate that in the long term, Bank Indonesia Sharia Certificates have a positive and significant effect on gross domestic product, but have no effect in the short term. Bank Indonesia Sharia Deposit Facilities in the long term or short term have no effect and are not significant on Gross Domestic Product, as well as the Islamic Interbank Money Market. These findings provide evidence that Islamic monetary operation instruments have not had a significant impact on Gross Domestic Product, so that a stimulus is needed to channel Islamic financing to the real sector in order to help increase economic growth.